Optimalisasi Strategi Pemasaran Digital Produk untuk Meningkatkan Penjualan pada Perusahaan UD. Dian Kurniawati - Muhammad Viky Fajar Ardiansyah; Mochamad Rizal Yulianto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The development of digital technology has encouraged MSMEs to begin implementing digital-based marketing. This community service project aims to determine the implementation of digital marketing strategies at UD. Dian Kurniawati, a MSME producing cooking spices in Tanggulangin, Sidoarjo, and its impact on marketing and sales. This research used a qualitative approach with a case study method through observation, interviews, and documentation. The results of the community service project indicate that the use of social media platforms like Instagram and TikTok can increase promotional reach, consumer interaction, and brand recognition, with TikTok being the most effective platform. Although sales through Shopee are still suboptimal, as most wholesale transactions are conducted through direct communication. In general, digital marketing has a positive impact on market expansion and sales movements, but further development is needed to maximize results.